Patients' Perceptions in Inpatient Service Quality and its Effect on Patient Loyalty with Patient Satisfaction as Mediation Variable - Octa Lidya Ghaisani Amin; Wisnu Untoro (Sebelas Maret Business Review, 2018)
This study aims to empirically test the patient's perception of the quality of inpatient services, and its effects on the loyalty of the patient, with patient satisfaction as a mediation variable. Data collection was performed by using five points Likert scales with judgment sampling approach. The study involved 160 patients of the dr. Prijonegoro Hospital, Sragen. Descriptive analysis was conducted followed by measurement analyses to ensure the validity and reliability. This research found that inpatient service quality has a significant positive effect on patients' satisfaction, patient satisfaction positively affect patients' loyalty, and patients' satisfaction partially mediated the effect of inpatient service quality on patient loyalty. Therefore, by improving the quality of services, it is expected that the patients were satisfied and then loyal after satisfied with inpatient service quality in the hospital.